Brain wavesclassification towardhuman emotion based on EEG signal - Ahmed, Mohammed Abdulkareem (2013)
The important role of communication between human’s brain and computer has been increased during the last years. In this research, the main focus of this thesis isanalysingbrain wavesthat associated with the internal emotion of human. The analysing processis achieved by reading the EEG signals from user brain.NIA deviceis used in this research to read the signals from the frontal lobe of the brain. This sturdy base on reading brain wave signals in order to be representedas an avatar facial expression. The aim of this research is to show the influence of alpha and beta brain waves toward emotion classification through EEG signal. In addition,the researchis analysing brain signals in order to represent happy and sad emotions. The classification of human emotion through brain computer interface can be interpreted through speed of brain waves signal. The velocity is used to calculate the speed of brain signals for each emotion. The results provedthat the velocity of sad emotion is faster than happy emotion. As a conclusion, this research shows the speed for each emotion which can be used to specify the internal emotion characteristic of a user. User emotion is represented as a facial expression of virtual human in 3D environment. These results can be used to create a good classification because it specifies the average of speed for each emotion.